SHAPING THE FUTURE: UNIVERSITY STUDENT´S PERCEPTIONS OF NANOTECHNOLOGY RISKS AND BENEFIT - Svrckova, Marika; Cakirpaloglu, Simona Dobesova; Holy, Ondrej; Zimmermannova, Jarmila; Schovankova, Tereza (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Nanotechnology plays a crucial role in the development of innovative products, yet public apprehension regarding its potential risks remains a significant barrier to its acceptance. This study investigates the knowledge, attitudes, and fears associated with nanomaterials among university students in the Czech Republic, aiming to inform policy formulation that aligns with public interests. Focusing on this demographic is essential, as university students are poised to influence future public discourse and innovation trends. Utilizing a cross-sectional online survey, we assessed perceptions of risks and benefits related to nanotechnology while considering sociodemographic factors such as gender and field of study. The sample comprised 107 university students aged 19-26 from diverse academic backgrounds. Our findings reveal a moderate overall familiarity with nanomaterials, while attitudes toward nanotechnology were generally positive. These insights highlight the necessity for targeted communication and educational strategies to address diverse viewpoints within society. As future decision-makers, understanding university students' perspectives is crucial for developing public policies that promote the responsible advancement and regulation of nanotechnology. Further research is needed to explore the underlying factors influencing these perceptions and to enhance public understanding of nanotechnology's benefits and risks.